2021
DOI: 10.1186/s40479-021-00152-y
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating research on childhood adversities, borderline personality disorder, and complex post-traumatic stress disorder

Abstract: Traumatic events of a long-lasting invasive, primarily interpersonal nature (e.g., childhood abuse, intimate partner violence) can have wide-ranging consequences across various life domains. This involves an increased risk of developing mental disorders, such as (complex) post-traumatic stress (PTSD, CPTSD) and borderline personality disorder (BPD). Both within and outside of these diagnostic boundaries, complex trauma has been associated with emotional dysregulation, dissociation, distrust, interpersonal prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…At a minimum, they require therapy that addresses the symptoms of both disorders. Furthermore, they may exhibit very high levels of problematic clinical features, including emotion dysregulation, self-harming behaviors, interpersonal difficulties, and dissociation (Cackowski et al, 2016; Harned, Rizvi, et al, 2010; Heffernan & Cloitre, 2000; Krause-Utz, 2021; Marshall-Berenz et al, 2011), and are at a high risk for suicide attempts (Yen et al, 2021). However, there is a lack of treatment programs that proved efficacious for both aspects of the dual diagnosis within a randomized controlled trial (RCT).…”
Section: Prevalence and Clinical Significance Of A Dual Diagnosis Of ...mentioning
confidence: 99%
“…At a minimum, they require therapy that addresses the symptoms of both disorders. Furthermore, they may exhibit very high levels of problematic clinical features, including emotion dysregulation, self-harming behaviors, interpersonal difficulties, and dissociation (Cackowski et al, 2016; Harned, Rizvi, et al, 2010; Heffernan & Cloitre, 2000; Krause-Utz, 2021; Marshall-Berenz et al, 2011), and are at a high risk for suicide attempts (Yen et al, 2021). However, there is a lack of treatment programs that proved efficacious for both aspects of the dual diagnosis within a randomized controlled trial (RCT).…”
Section: Prevalence and Clinical Significance Of A Dual Diagnosis Of ...mentioning
confidence: 99%
“…Años más tarde, Judith Herman (1992) observó los síntomas de personas sometidas a situaciones extremas (violencia doméstica, sexual o abusos infantiles), que no encajaban en el diagnóstico de TEPT, proponiendo el Trastorno de Estrés Postraumático Complejo (TEPTc), con seis características: alteración en la regulación de los afectos, de la conciencia, de la autopercepción, percepción alterada del agresor, problemas en las relaciones y cambio en el sistema de valores. Su origen radica en experiencias de larga duración, continuas, acumulativas, invasivas, de tipo interpersonal (abuso sexual infantil, maltrato, abandono o negligencia ejercida por los cuidadores, violencia doméstica y/o de género, explotación sexual, genocidios, tortura…), con frecuencia vividas en edad infantil (aunque pueden producirse en cualquier momento evolutivo), en ambientes de alto riesgo de los que la persona no puede escapar (Felding et al, 2021;Herman, 1992;Krause-Utz, 2021). Es la continuidad, el carácter interpersonal y la imposibilidad de huida lo que lo diferencia del TEPT, cuyo desencadenante suele ser un evento único o limitado en el tiempo, de carácter interpersonal o no.…”
unclassified
“…La presencia de acontecimientos adversos en la infancia es un factor de riesgo, aunque ni necesario ni suficiente para explicar el surgimiento del TLP, ya que ese factor no es capaz de dar solución al dilema de por qué algunos supervivientes de abusos o maltratos desarrollan TLP mientras que otros no. Que la presencia de tales acontecimientos no sale gratis es cierto, pero la idea de que determinados traumas infantiles conllevarán trastornos específicos (como el TLP) carece de fundamento, ignorando el principio de equifinalidad/multifinalidad o multideterminación (Paris, 2015;Talarn et al, 2013) y la interrelación con factores biológicos y de temperamento que ejercen como elementos de vulnerabilidad (Bozzatello et al, 2021;Goodman y Yehuda, 2002;Krause-Utz, 2021). Así, siendo eventos que pueden agravar los síntomas TLP y su curso, empeorando el pronóstico, no son imprescindibles para su diagnóstico (a diferencia del TEPT y TEPTc).…”
unclassified
“…One possible explanation for these findings could be the compounding effect of impairment individuals are experiencing due to multiple disorders. For example, the sense of impairment pertaining to PTSD, in particular, has been highlighted in multiple studies (i.e., Cackowski et al, 2016;Harned et al, 2020;Krause-Utz, 2021;Yen et al, 2021) with each claiming that a dual diagnosis of PTSD and BPD is associated with higher levels of emotional dysregulation, self-harming, and suicide attempts compared to individuals with either PTSD or BPD only.…”
Section: Discussionmentioning
confidence: 99%
“…Dual diagnosis of PTSD and BPD demonstrate a high need for treatment given that these individuals exhibit high levels of emotion dysregulation, self-harming behaviors, interpersonal difficulties, and suicide attempts (Cackowski et al, 2016;Harned et al, 2020;Krause-Utz, 2021;Yen et al, 2021). Among individuals with BPD who seek treatment, prior studies have found that over 50% of these individuals met the criteria for PTSD suggesting that individuals with both diagnoses may be contributing factors to seeking treatment (Cackowski et al, 2016;Harned et al, 2010).…”
Section: Borderline Personality Disorder and Comorbid Disordersmentioning
confidence: 99%